Daylighting in Semi-open Atrium for Sustainability: Case Studies of Educational Buildings in Bangkok Suburbs - Atthakorn, Songpol (Journal of Architectural/Planning Research and Studies (JARS), 2021)
Since high-quality daylighting in the semi-open atriums in educational buildings could promote learning efficiency, well-being, and reducing the use of energy. Therefore, the study of appropriate daylighting in atriums is substantial for the design consideration of sustainable architecture.. The objective of this research was to find the relationships between the physical forms of the atriums which affect the daylight qualities in the atriums, to develop the knowledge of daylighting in sustainable buildings. The research started with analyzing of 4 case studies to know the dimensional proportion and characteristics of the case studies, such as openings, well indexes (WI), and the compositions of the atriums. Next, evaluating daylight performances inside the atriums by computer simulation. Then, comparing the results of the quantities and qualities of daylight inside the case studies. Lastly, discovering the relationship between physical characteristics and the results of daylight evaluation. The important indicators are; luminance (I), illuminance (E), uniformity of light (U), daylight factor (DF), useful daylight illumination (UDI), spatial daylight anatomy (sDA), annual sunlight exposure (ASE), and daylight glare probability (DGP). The results found that; 1) The proportional area of the skylight affects daylight in the atrium most. 2) The wall openings at the floor level help control the uniformity of light in the atrium. 3) The well index value affects directly the illuminance in the atrium. 4) Shadings of the above balcony, blind areas in the atrium, and light reflection from building surfaces affect the illuminance on the working plane and the uniformity of light in the atrium. 5) Daylight exceeded 3000 lux could course glare. 6) The evaluation of daylight in the vertical plane and the annual daylight simulation with climate-based daylight modeling (CBDM) helps to visualize more realistic perceptions. Therefore, the design of daylighting in semi-open atriums should consider; 1) the effects of sunlight radiation in the atriums 2) the amount of daylighting concerning the proportion of the atriums, 3) the daylighting qualities that do not cause glare effect, 4) the internal facade compositions that promote daylight distribution, and 5) the arrangement of interior space due to daylight effects.